2019
DOI: 10.1111/jtxs.12385
|View full text |Cite
|
Sign up to set email alerts
|

Textural, mechanical, and microstructural properties of restructured pimiento alginate‐guar gels

Abstract: Textural, mechanical, microstructural, and thermal properties of reconstituted pimiento alginate‐guar gels subjected to thermal and mechanical stresses during pasteurization process were investigated. Alginate‐guar gelling system at ratio 2:1 at different calcium chloride concentrations (2–8%) and varying acid conditions including citric and lactic acid 1% were evaluated. Textural profile analysis parameters viz. hardness, springiness, gumminess, cohesiveness, adhesiveness as well as mechanical properties, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…Increasing in hardness can be related to the more cross‐linking of the alginate by calcium, which improves the gel strength. Similar results were also reported in our previous work (Mousavi et al, ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Increasing in hardness can be related to the more cross‐linking of the alginate by calcium, which improves the gel strength. Similar results were also reported in our previous work (Mousavi et al, ).…”
Section: Resultssupporting
confidence: 93%
“…The pimiento strips were prepared according to our previous work (Mousavi, Rafe, & Yeganehzad, ). In brief, pimiento puree was thoroughly mixed with deionized water, potassium sorbate (0.1 g), sodium alginate, and guar for 5 min at 21–48 g over a juicer blender (SHARP ‐ COUNTERTOP BLENDER SBTI172G) in order to achieve no lumps and the mixture became homogenous.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that the comparison of the mechanical resistance at different temperatures (80, 110, and 130 °C), for the same period (0, 5, 10, 15, and 20 min) of incubation, shows that a higher resistance is always obtained at the higher temperature. A previous study also reported that the hardness of the alginate-guar gels mixed with pimiento pulp significantly increased when applying thermal treatment (80 °C for 15 min) [24]. The authors reported that the increase in hardness of the alginate-guar gels originated from the occurrence of gel shrinkage, making them more compact during heat treatment [24].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study also reported that the hardness of the alginate-guar gels mixed with pimiento pulp significantly increased when applying thermal treatment (80 °C for 15 min) [24]. The authors reported that the increase in hardness of the alginate-guar gels originated from the occurrence of gel shrinkage, making them more compact during heat treatment [24].…”
Section: Resultsmentioning
confidence: 99%